Adsorption of CO2 Molecule on the (MgO)\(_9\) and (CaO)\(_9\) Nanoclusters - Fathi Hassan Bawa (Progress in Chemical Science Research Vol. 5, 2022)
The aim of the present study is to address the reaction of CO2 on MgO and CaO surfaces to form carbonate (CO32-). In addition, an effort is made to characterise the proposed CO2/(MgO)9 adsorption by calculating its vibration frequency and compare with experiment. A subsequent study will address the adsorption of SO2 onto (MgO)9 and (CaO)9 cluster models. Density functional theory model simulations are used to study the binding configurations of CO2 on the (MgO)9 and (CaO)9 cluster models. The results show that CO2 adsorbs as monodentate on MgO and CaO terrace site leads to formation of surface carbonates CO32-. Marginal differences in the binding stabilities between the CO2 molecule and surface O2- site were found to be significantly similar. The estimated adsorption energies are 1.47 eV and 1.52 eV at the (MgO)9 and (CaO)9 clusters, respectively. The similarity in binding energies is discussed in terms of cluster electro-positivity. Adsorbed CO2, to (MgO)9 surface vibration frequencies are calculated and compared to the experiment. It is concluded that in the absence of Madelung potential, as the case for clusters, the local Lewis basicities at the O2-surf sites display similar strengths irrespective of the different alkaline earth cations.